The most frequently used judo techniques in accordance with current sport rules - Gardasevic, N.; Stankovic, N. (Fis Communications 2019, 2019)
The research aimed to determine which judo techniques are most commonly used in competitions, in accordance with current rules prescribed by the World Judo Federation (IJF). The analysis included 13 studies, which analyzed 34 judo competitions from 1981 to 2014. Leg judo techniques (Ashi waza) have been found to be the most commonly used techniques from 1981 to 1999, compared to other groups of techniques, especially for heavyweight competitors. In the period from 2000 to 2009, hand judo techniques (Te waza) had the most common application, and after the rule changes from 2009 and 2010, there would be a equal application of hand and leg judo techniques. The equilibrium between the use of hand and leg judo techniques continued after the 2013 rule change. The general conclusion is that the rule changes influenced what techniques the judokas commonly use during the match. Individually, the following techniques are most commonly used in judo in the studies analyzed: Uchi mata and Seoi nage (most often), Ko uchi gari, Ko soto gari, Kata guruma, Te guruma, Kuchiki taoshi, Morote seoi nage, Ippon seoi nage, O uchi gari, Harai goshi, Tani otoshi, O soto otoshi, De ashi barai and others. The conducted analysis can have practical application and contribute to judo coaches in planning the training process, especially in the part of planning the strategy and tactics for competition.